Rooftop Farming – An Overview - Debangshi, Udit; Mondal, Ramyajit (Chronicle of Bioresource Management, 2023)
The land has become an expensive unit in India due to its diversion following urbanization, industrialization etc. Further, migration and settlement of rural people in urban areas has been increasing at an alarming rate. It is estimated that, in India, 40.76% of the population is expected to reside in urban areas by 2030. Thus, it is going to increase pressure on natural resources and production volume in the rural areas due to increasing demand for food in urban areas. The cultivated land in urban areas is already limited. Hence, the rooftop area available on the urban households/government and non-government offices can be exploited to produce various crops. This Greener rooftop is a like a psychological relief centre, which makes households stress-free. This environmentally and economically sustainable method to promote food security, food quality and reduce the carbon foot-prints, has emerged as a viable option in the recent years.